Anterior Cruciate Ligament Repair With Suture Tape Augmentation Using Self-Tapping Knotless Anchors - Justin Jabara, M.D.; Marcus Trotter, M.D.; Jamie E. Confino, M.D.; Alan L. Zhang, M.D. (Arthroscopy Techniques)
Anterior cruciate ligament (ACL) repair strategies continue to evolve as clinical outcomes have shown comparable results to ACL reconstruction in select patients. There is heterogeneity in ACL repair techniques, including knotless suture anchor fixation, suspensory cortical button fixation, and addition of suture tape for augmentation. Biologic scaffold augmentation, such as bridge-enhanced ACL repair, have been under investigation given its potential to aid in ligamentous healing. We present our technique for primary ACL repair utilizing nonabsorbable polyether ether ketone (PEEK), Stryker AlphaVent Knotless self-punching suture anchors, and suture tape augmentation. The bridge-enhanced ACL repair (BEAR) scaffold implant can also be incorporated into the repair without significant alteration of the technique, which improves intraoperative efficiency while minimizing extraneous steps.